BIODETERIORATION OF CELLULOSE MATERIALS IN KARINGOTE, NILESWARAM, KAVVAYI AND RAMAPURAM BACKWATER SYSTEMS OF KERALA - NAIR, N. BALAKRISHNAN (Journal of Indian Fisheries Association, 2015)
The hydrographic conditions prevailing in an estuarine system along the southwest coast of India are described. The nature of destruction of timber in these backwaterÂ·s has been examined in detail which revealed the existence of 8 species of shipworms, 2 species each of Jlholads and isopods. The shipworms arc represented by Dicyathifer mmmi, Lyrodus pedicellatus, Teredo furcifera, Teredo clappi, Nausitora dunlopei, Bankia carinata, Bankia campanellata; the J>holads by Martesia striata and Martesia (Particoma) nairi; and the isopods by Sphaeroma terehrans and Sphaeroma annamlalei. The incidence and relative abundance of these pests arc discussed in relation to the salinity profile of the estuary.